Eksplorasi dan Inventarisasi Tumbuhan Obat untuk Pengobatan Tradisional di Desa Bunga Sampang, Simalungun - Tarigan, Jeyca Pradinta; Rahman, Abdul (Universitas Medan Area, 2025)
Indonesia has biological and cultural richness which is reflected in the traditional use of medicinal plants. This study aims to explore and inventory the types of medicinal plants used by the people of Nagori Bunga Sampang Village, Purba District, Simalungun Regency, North Sumatra. The method used is a qualitative exploratory approach with a descriptive ethnobotanical method. Data collection was carried out through semi-structured interviews, direct observation, documentation, and literature studies. The results of the study show that there are 16 species of medicinal plants that are used to treat various health complaints such as fever, ulcers, cough, joint pain, and degenerative diseases. The most commonly used part of the plant is the leaves, followed by fruits, roots, stems, and bark. In addition to demonstrating ethnopharmacological potential, this practice also reflects traditional knowledge systems that are passed down from generation to generation. This research emphasizes the importance of documentation and preservation of local knowledge as part of the protection of communal intellectual property.